Pelatihan Pengolahan Limbah Kulit Kopi untuk Pakan Ternak Ruminansia di Desa Ngembat, Gondang, Mojokerto - Khaleyla, Firas; Kuswanti, Nur; Qomariyah, Nur; Purnama, Erlix Rakhmad (LPPM Universitas Flores, 2023)
Coffee is one of Indonesia's leading national commodities. However, coffee cultivation produces organic agricultural waste in the form of coffee husks. Based on its content, coffee husk waste still has the potential to be processed into other useful products, one of which is animal feed. The occupation of Ngembat village apart from cultivating coffee, are also raising ruminants, so the solution offered wasto carry out training on making animal feed with coffee husk waste. Community service activity was carried out on July 29, 2023 at the Ngembat Village Hall. The activity was attended by 17 residents of Ngembat village. The activity began with material regarding basic nutritional needs for ruminants and the content of coffee skins, then continued with participants practicing coffee husk fermentation. Coffee skin waste was fermented with Trichoderma sp. and the resulting product was evaluated after 5 days. The activity had received positive response from all participants and the product results of the participants had been as expected. With the implementation of training on making animal feed from coffee skin waste, it is hoped that it can reduce agricultural waste resulting from coffee cultivation carried out by the people of Ngembat village.